Contribution to "Deliverable 4: Activity 6: Pilot Demonstrations: Pilot testing, 2nd milling campaign" - Ribeiro, Belina (2016)
Report for Deliverable 4: Activity 6 of MEDOLICO Project - Mediterranean Cooperation in the Treatment and Valorisation of Olive Mill Wastewater, EU Programme ENPI-CBCMED I-B/2.1/090